Asynchronous-bit-rate differential phase-shift-keying - You-Cheng Lin; Kuan-Wei Hu; Hsing-Yi Huang; Yueh-Hsun Yang; You-Xin Wang; Shih-Chang Hsu; Chih-Hsien Cheng; Atsushi Matsumoto; Kouichi Akahane; Yuh-Renn Wu; Hao-Chung Kuo; Gong-Ru Lin (APL Photonics)
An adaptive differential-phase-shifting (DPS) quantum key distribution (QKD) protocol improved by encoding asynchronous-bit-rate with harmonic clock tunability, decoded by shortened delay-line interferometer (DLI) with enhancing stability, and received by single-photon detection with long hold-off is demonstrated to realize low-erroneous transmission. To achieve long-term stabilized visibility with a maintained quantum bit-error-ratio (QBER) and secure key rate, the shortened and polarized DLI enlarges its free-spectral range (FSR) and reduces its power-to-wavelength slope (δP/δλ) to suppress its sensitivity to thermal gradient, channel leakage, and wavelength disturbance. Extremely low power and wavelength drifts of ΔP/P < ±0.02% and Δλ/λ = ±6.45 × 10−8 can be achieved, even when using a single-mode QKD carrier with a relatively broadened 300-kHz linewidth. Flexibly expanding the 1-bit-delay FSR of the polarized DLI from 0.04 to 1.00 GHz improves its immunity to environmental disturbances, enabling the DPS-QKD decoding with 210–213 patterns, 3.2% QBER, and 17.46-kbit/s under 0.22 photon/pulse in average. The asynchronous-bit-rate DPS-QKD protocol enables harmonic expansion of DLI’s FSR at limited single-photon avalanche detector’s bit rate, which lengthens the duration of stable visibility to support long-pattern DPS-QKD.